Warlock : a novel of ancient Egypt - Smith, Wilbur A. (Smith, Wilbur A. Ancient Egypt series, 2001)
TAfter the death of his beloved Queen Lostris, Taita heads to the harsh deserts of North Africa to devote himself to a study of the occult, to become a warlock, and to fulfill his destiny to protect the dynasty of Lostris from the evil that threatens ancient Egypt.